Early sacubitril/valsartan use associated with reduced atrial fibrillation risk in patients with acute myocardial infarction complicated by mitral regurgitation: a retrospective cohort study - Yin, Hongtao; Zhou, Yanqing; Zhou, Yingjun; Ren, Lin; Ma, Lixiang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPatients with acute myocardial infarction (AMI) complicated by mitral regurgitation (MR) experience a substantially elevated risk of atrial fibrillation (AF). Evidence remains limited regarding whether early administration of sacubitril/valsartan confers additional protection against new-onset AF in this high-risk population to traditional ACEI/ARB therapy.ObjectiveTo evaluate the impact of early sacubitril/valsartan therapy on the 1-year cumulative incidence of AF in patients with AMI complicated by MR.MethodsIn this single-center retrospective cohort, 1,065 in-patients with AMI complicated by MR (June 2021–December 2023) were categorized by discharge prescription into the Sacubitril/Valsartan group (n = 427) or the ACEI/ARB group (n = 638).The primary endpoint was new-onset AF within 1 year. Cumulative incidence was estimated using the cumulative incidence function (CIF) and compared with Gray's test. Associations were evaluated using Fine–Gray subdistribution hazard models [subdistribution hazard ratios (sHR)] and multivariable Cox proportional hazards models [hazard ratios (HR)]. To mitigate confounding, 1:1 propensity score matching (PSM) was performed, and analyses were repeated in the matched cohort. Prespecified subgroup analyses were performed to assess treatment-effect consistency.ResultsDespite a higher baseline risk profile in the Sacubitril/Valsartan group, the 1-year cumulative incidence of AF was lower than in the ACEI/ARB group (CIF 10.8% vs. 17.9%; Gray's test P = 0.002). In competing-risk analysis, sacubitril/valsartan was associated with a reduced risk of AF (sHR = 0.56; 95% CI 0.39–0.81; P = 0.002), concordant with the multivariable Cox model (HR = 0.55; 95% CI 0.38–0.81; P = 0.003). After PSM, the association persisted in both the competing-risk analysis (sHR = 0.63; 95% CI 0.40–0.94; P = 0.025) and the Cox model (HR = 0.63; 95% CI 0.41–0.96; P = 0.030). Subgroup analyses demonstrated consistent benefits across all prespecified strata.ConclusionEarly sacubitril/valsartan use was associated with reduced 1-year AF risk vs. ACEI/ARB in AMI complicated by MR, suggesting a potential role in this population; prospective trials are needed to confirm causality.